Efficacy and Safety of Sacubitril/Valsartan Versus Amlodipine in Japanese Patients With Essential Hypertension: A Randomized, Multicenter, Open‐Label, Noninferiority Study (PARASOL Study) - Koichi Yamamoto; Daisuke Yarimizu; Ayano Shimanishi; Shunsuke Eguchi; Kazuma Iekushi; Yoichi Takami; Yoichi Nozato; Kazuomi Kario; Hiromi Rakugi (The Journal of Clinical Hypertension)
ABSTRACT Sacubitril/valsartan, an angiotensin receptor‐neprilysin inhibitor, has demonstrated a superior blood pressure‐lowering effect compared with renin‐angiotensin system inhibitors in several clinical trials. However, there has been no available evidence on the comparison between sacubitril/valsartan and calcium channel blockers (CCBs), a well‐established class of antihypertensive drugs. In this open‐label, multicenter study, we aimed to demonstrate the efficacy and safety of sacubitril/valsartan versus amlodipine, one of the most widely used CCBs, after 8 weeks of treatment. A total of 359 Japanese patients with essential hypertension (office systolic blood pressure [SBP] ≥ 150 to < 180 mmHg), aged 18–79, were randomly assigned to receive either once‐daily sacubitril/valsartan 200 mg or once‐daily amlodipine 5 mg in a 1:1 allocation ratio. The primary endpoint was the noninferiority of sacubitril/valsartan compared with amlodipine in mean change in 24‐h SBP from baseline to Week 8, followed by a significance test as a secondary endpoint analysis. The mean change in 24‐h SBP in sacubitril/valsartan was noninferior to that in amlodipine (between‐treatment difference −0.62 mmHg [95% confidential interval: −3.23 to 1.98; p = 0.003 for noninferiority; independent t‐test with noninferiority margin 3.0 mmHg]), with no significant difference observed (p = 0.637). There was no significant difference in the incidence of adverse events (AEs). These results suggested that the blood pressure‐lowering effect of sacubitril/valsartan is comparable to that of amlodipine, with no marked differences in tolerability between the two groups. Sacubitril/valsartan, a potent antihypertensive drug comparable to amlodipine, is expected to improve blood pressure control in clinical practice.